Educating teachers changing the nature of pedagogical knowledge - Smyth, John, 1944- (London ; New York : Falmer Press, 1987)
1. Education--study and teaching 2. Teachers--Training of
Includes index.
Includes bibliographies and index.
Fourth year high school and above
Keywords: Education -- Study and teaching; Teachers -- Training of